Appropriate Tax Measures to Promote the Production and Trade of Colored Stones in Thailand - Duangphastra, Chackrit (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
Various global leading countries of gems production and trade have used tax measures to promote the development of gems industry. The objectives of the research are to collect information of tax burden, strengthes, weaknesses, opportunities, and threats of tax measures imposed on Thai colored stone producers and traders, and propose appropriate tax measures for Thai colored stones producers and traders by using qualitative and quantitative methods. The research suggested government to maintain the removal of import duties and value added tax imposed on importing and selling rought and polished colored stone as well as increase public relation activities to enable entreneurs know how to effectively utilize such tax privileges. In addition, the government should replace the current tax collection practices on corporate income tax and personal income by introducing lump sum tax collection based on revenue earned from colored stone trade. The change in such income tax collection measure would equip Thai government to expand tax base, reduce the usage of general discretion of individual officials in evaluating collectable tax on colored stone tade, and enable entrepreneurs to accurately estimate tax expense.